Kesenjanganantara Pendidikan Pesantren dan PTAI - Humaidi, Anis (Didaktika Religia, 2014)
This article aims at analyzing and comparing education system of Islamic boardingSchool and Islamic university. There are the same goals between those bothinstitutions, that is to create Ulama’. However, the outputs of both institutionsare quite different, even in giving the scholar’s degree. For the graduates of theIslamic boarding school are called Kyai, on the other hands, the graduates of theIslamic University are known as religious scholars. But the two terms refer to thesame meaning, Ulama’. The graduates of the Islamic boarding school are usuallymore proficient in mastering classical texts. So they tend to be more textual orscriptural in handlingsome particular problems. On the contrary, the graduatesof Islamic university tend to think contextually and critically.Nevertheless, unlikethe graduates of the Islamic boarding schools, most of them are not well qualifiedinundertaking the classical resources dealing with religious law or theology ingeneral. So there has been an apparent discrepancy between the two sides. Howcould we overcome this discrepancy?